2007
DOI: 10.1152/ajpheart.00776.2007
|View full text |Cite
|
Sign up to set email alerts
|

IKKβ inhibition attenuates myocardial injury and dysfunction following acute ischemia-reperfusion injury

Abstract: Moss NC, Stansfield WE, Willis MS, Tang R, Selzman CH. IKK␤ inhibition attenuates myocardial injury and dysfunction following acute ischemia-reperfusion injury. Am J Physiol Heart Circ Physiol 293: H2248-H2253, 2007. First published August 3, 2007;. doi:10.1152/ajpheart.00776.2007.-Despite years of experimental and clinical research, myocardial ischemia-reperfusion (IR) remains an important cause of cardiac morbidity and mortality. The transcription factor nuclear factor-B (NF-B) has been implicated as a key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 38 publications
4
77
0
1
Order By: Relevance
“…In vivo transfer of NF-κB decoy oligodeoxynucleotides to bind the transcriptional factor blocking inflammatory gene activation, reduced the extent of myocardial infarction following reperfusion suggesting a crucial role for NF-κB in the regulation of the post-infarction inflammatory response [78]. In addition, treatment with an IKKβ inhibitor attenuated IκBα phosphorylation reduced infarct size, improved cardiac function and decreased proinflammatory cytokine levels in a model of reperfused infarction [79]. Furthermore, transgenic mice with cardiac-specific expression of a dominant-negative IκBα resulting in inhibition of cardiomyocyte NF-κB activation, exhibited significantly decreased infarct size in a model of reperfused infarction [80], and NF-κB p50 null mice had improved early survival and reduced left ventricular dilatation after non-reperfused infarction [81].…”
Section: Activation Of the Nf-κb Systemmentioning
confidence: 98%
“…In vivo transfer of NF-κB decoy oligodeoxynucleotides to bind the transcriptional factor blocking inflammatory gene activation, reduced the extent of myocardial infarction following reperfusion suggesting a crucial role for NF-κB in the regulation of the post-infarction inflammatory response [78]. In addition, treatment with an IKKβ inhibitor attenuated IκBα phosphorylation reduced infarct size, improved cardiac function and decreased proinflammatory cytokine levels in a model of reperfused infarction [79]. Furthermore, transgenic mice with cardiac-specific expression of a dominant-negative IκBα resulting in inhibition of cardiomyocyte NF-κB activation, exhibited significantly decreased infarct size in a model of reperfused infarction [80], and NF-κB p50 null mice had improved early survival and reduced left ventricular dilatation after non-reperfused infarction [81].…”
Section: Activation Of the Nf-κb Systemmentioning
confidence: 98%
“…In addition, blocking MyD88, the downstream adapter of TLR-4 signaling, displays similar protection against myocardial injury (51). Moreover, several studies have underlined the role of the NF-κB pathway in cardiac hypertrophy and inflammation (52)(53)(54)(55). Since the NF-κB pathway is one of the major proinflammatory pathways to be induced by TLR activation, it is likely that a subgroup of inflammatory genes, including Cfb, is induced by TLR-4 activation upon myocardial injury.…”
Section: Figurementioning
confidence: 99%
“…Recent studies noted that NF-B blockade by inhibiting IKK-␤ activity decreased myocardial injury and preserved cardiac function following ischemia-reperfusion (26), which supports the concept that the inflammatory response participates in the development of heart failure (42). Our results show that p-IKK-␤ increases in diabetes, but the blockade of NF-B and oxidative stress and the genetic deletion of TNF-␣ attenuated p-IKK-␤, suggesting that the phosphorylation of IKK-␤ increases in diabetic mice by the activation of oxidative stress and TNF-␣.…”
Section: Roles Of Interaction Of Tnf-␣ and Nf-b Signaling In Type 2 Dmentioning
confidence: 99%
“…IKK-␤, the molecular target of NaSal, is associated with the rise of insulin resistance (7,43). Recent work suggests that a specific antagonism of the NF-B inflammatory pathway through the inhibition of IKK-␤ reduces acute myocardial damage following ischemia-reperfusion injury (26) and that insulin action plays a critical role in reducing myocardial infarct size by increasing cardiac myocyte metabolism (5,8,29). We previously found that TNF-␣-activated Jun NH 2 -terminal kinase (JNK), which mediates O 2 Ϫ production and impairs endothelium-dependent, nitric oxide (NO)-mediated vasodilation in coronary arterioles (45).…”
mentioning
confidence: 99%